The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1002/jrs.4733
|View full text |Cite
|
Sign up to set email alerts
|

Surface anchoring mode‐dependent hydrolysis reactions of hydrazone groups on gold examined by pH‐dependent Raman spectroscopy

Abstract: We conducted a comparative study of the pH‐dependent anchoring behaviors of 3‐methyl‐2‐benzothiazolinone hydrazone (3M2BH) and benzophenone hydrazone (BPH) on gold nanoparticles (AuNPs) by means of interfacial Raman spectroscopy. We found that several bands of 3M2BH in the highly alkaline pH region disappeared as the colloidal conditions became more neutral and acidic. The vibrational band at 919, 1174, and 1222 cm−1 at pH 10.0 disappeared below pH 9.2, which may be because of the hydrolysis reactions that cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…The SERS spectrum of GLY appeared to be relatively weak with its amino group interacting with Au surfaces. In the SERS spectrum of hydrazine on AuNPs, we could not observe a strong hydrazone linkage-related N-N stretching mode at 919 cm − 1 or N-H bending modes at 1174 and 1222 cm − 1 [34]. …”
Section: Resultsmentioning
confidence: 99%
“…The SERS spectrum of GLY appeared to be relatively weak with its amino group interacting with Au surfaces. In the SERS spectrum of hydrazine on AuNPs, we could not observe a strong hydrazone linkage-related N-N stretching mode at 919 cm − 1 or N-H bending modes at 1174 and 1222 cm − 1 [34]. …”
Section: Resultsmentioning
confidence: 99%
“…By investigating the SERS spectra of such species in aggregated gold nanoparticles, Gadogbe et al [232] concluded that the molecules are Ly and Joo [235] reported the SERS behavior of 3-methyl-2-benzothiazolinone hydrazone, and benzophenone hydrazone anchored on gold nanoparticles, showing the occurrence of hydrolysis of the =N-NH 2 group below pH 9.2.…”
Section: Sers Of Adsorbed Moleculesmentioning
confidence: 98%
“…Adsorption of organic thiols and carboxylic acids on metal colloids is an issue of great interest in surface science, which have been recently investigated by employing surface‐enhanced Raman scattering (SERS) . The high sensitivity of this technique yields a detailed information on the mechanism of the molecular adsorption, allowing, for example, to know which functional groups bind the metal surface .…”
Section: Introductionmentioning
confidence: 99%
“…Adsorption of organic thiols and carboxylic acids on metal colloids is an issue of great interest in surface science, which have been recently investigated by employing surface-enhanced Raman scattering (SERS). [1][2][3][4][5][6][7][8][9][10] The high sensitivity of this technique yields a detailed information on the mechanism of the molecular adsorption, allowing, for example, to know which functional groups bind the metal surface. [4] In this context, p-hydroxybenzoic acid (PHBA) and p-mercaptobenzoic acid (PMBA) are molecular probes of interest for the detection of surface plasmons, [5,10] mainly because of their applicability to attain large SERS intensities involving silver and gold nanoparticles.…”
Section: Introductionmentioning
confidence: 99%